A Phase III randomised trial of the immunogenicity and safety of quadrivalent versus trivalent inactivated subunit influenza vaccine in adult and elderly subjects, assessing both anti-haemagglutinin and virus neutralisation antibody responses. Issue 40 (25th September 2018) - van de Witte, Serge; Nauta, Jos; Montomoli, Emanuele; Weckx, Jos
Highlights: The immunogenicity of QIV was non-inferior to the matched influenza strains in TIV. The immunogenicity of QIV was superior to the alternate-lineage B-strains in TIV. The results of the HI assay correlated with the results of VN assay. QIV was well tolerated with a similar safety profile to that of TIV. Abstract: Background: Trivalent influenza vaccines (TIVs) offer substantial protection against matching B-strains, however, protection against alternate-lineage B-strains may be enhanced by adding a second B-strain in quadrivalent influenza vaccines (QIVs). In this Phase III, double-blind, multicentre, randomised study, the immunogenicity and safety of subunit inactivated QIV versus TIV was assessed in adult (aged ≥18 to ≤60 years) and elderly (aged ≥61 years) subjects by analysing a combination of haemagglutinin inhibition (HI) and virus neutralisation (VN). Methods: Subjects (n = 1980) were recruited off season (2015/2016) from 20 centres in five European countries and randomised to receive either QIV (n = 1538), TIV with B-strain of the Victoria lineage (n = 221) or TIV with B-strain of the Yamagata lineage (n = 221). The primary aim was to demonstrate non-inferiority of QIV to TIV for immunogenicity against matched influenza strains based on post-vaccination HI titres. Secondary aims were to show superiority of QIV to TIV for immunogenicity against alternate-lineage B-strains and to characterise the immune response by reverse cumulative distribution (RCD) curves of antibody titres and derived serological parameters for HI and VN. Reactogenicity and occurrence of adverse events were assessed post-vaccination. Results: QIV elicited a non-inferior immune response for matched strains (upper limit of 95% CI for HI geometric mean ratios [GMRs] <1.5) and a superior response for alternate-lineage B-strains (HI GMRs < 1; p < 0.0001) versus TIV. RCD curves demonstrated that post-vaccination HI and VN titres were higher for QIV versus TIV for both alternate-lineage B-strains. Seroconversion rates and geometric mean fold increases of the VN assay were consistent with the HI assay for all strains in QIV. Reporting rates of local and systemic reactions were similar in both vaccine groups. Conclusions: QIV was non-inferior in immunogenicity to TIV for matched strains and superior to the alternate-lineage B-strains in TIV. Safety and tolerability profiles of QIV and TIV were comparable.